Synthesis OF Ligands O.F BIS-Oxadiazole Triazole Witb Open OR Close Sides and Their Complxes With (Ctlf, Pdll) -
A OUI,tiper of LWW lig_;:tnds .of ppen sides. of Bis-’Oxad1azoJeÂ· andÂ· Bis-triazole derived from dichloroetbane and [Bis 0-ohloro et!:ty) = :=:: = ether)] (BCEE)’ wersynthesi:zed. These inelude: 1, 4- bis[-3thio- 2 - . (ChloroÂ·ethyl)l1 1;4 - oxadiazole ......yl] butane (-L I);1 4 B’is phenl- 3thio - 2 ( 2 -chloroethoxy)- ethyl 1 3A- oxadiazole-5yl) butane (t2)’l His [4-_ph nyl -3thio(chloro thy:l)1; ,4 - ttiazoJ Syl] methane (L1) Bis[ phehyl-3, thi-0- 2( 2-chloroethoxy) ethyl 1, 2:,4- triazole- 5yl] : = methane (L:4) 1,. 2- bi[<.1- . pnenyl: -3 tbio- 2 (cb.loroethy1 L,2,4- triazo1e - 5yl]ethane; :lll()T!O.di.mefuyl sulphoxide (Ls), l,2- Bis [4.Â pbenyl -3 thio- 2( 2- chloroethoxy) ethyl- 1,2,4 - triazole - 5) ] ethane (L ) and 1,4 - Bis [4-phenyl """’"3 thio-2 ..(chloroe-thyl) 1,2,4- triazole - SyL] butane; mono dimetby.ls Jiphoxide (L 7) re pecti.vely. Thi was prepared Â£tom the rea tiqn of Â· one mple of the fol’lowing Â¢ompounds: 1, 4: - Hi\5 t2-thio- 1- 3.4 -oxadiazole 5yiJ ,butane (M.1), Bis- (4-phen:yl-3Ahio1-1 2.4 -friazole -S.ylmethane (M 2), 1, 2– is (fhphÂ·nyl-J- thiol-l ,t.4- triazci’le-5yl) ethane (fv[3) and 1 ,4His [4-phenyl -J. - .t hio - 1. 2, 4 - tri l mle - 5 ylJ butane . ( 4) re-spectively lith two moleof qichl oethane and (BCEE) and two moles of s6dium hydroxide. In. :adtt:ition new c-lose lig-ands of BlsÂ o adiazofam;! B.is-triaz9-le derivati ves with !)ot;ne- of th. ir coro._pl es bf coppei’Â· and palladium were synthesLzed. The ligands.. were , number=3, journal=Ibn AL-Haitham Journal For Pure and Applied Sciences, author=Me.hdi, W.K. and Musa, F. H. and Fadhel, H. A., year=2017, month=Sep., pages=93–116